Online vibration state identification of multi-rigid-body system based on self-healing model - Guoyu Wang; Yang Tian; Chunming Hou; Kewei Tong (Scientific Reports)
Abstract The paper proposes a multi-rigid-body system state identification method based on self-healing model in order to improve the accuracy and reliability of CNC machine tools. Firstly, considering the influence of the joint surface, the Lagrange method is used to establish the mechanical model of the multi-rigid-body system. We input acceleration information and use the second-order modulation function to complete the online real-time identification of the joint surface parameters, thereby establishing the self-healing mechanical model of the multi-rigid-body system. Then, the system state equation is established by Kalman filter method based on the self-healing mechanical model, and the full information identification of multi-rigid-body system is realized by using acceleration information as input. Finally, the VMC850 vertical machining center is taken as an example to verify that the above method has high accuracy. The online state identification method proposed in this paper can provide real-time data basis for machine tool accuracy compensation and health state estimation.